Protecting human rights through fundamental principles of administrative procedures in Eastern Europe - Tina Sever (DANUBE: Law, Economics and Social Issues Review, 2014)
Administrative procedures (APs) are tools to protect fundamental human rights in statecitizen relations. As the modernization of public administration regulation is undergoing a transformation in the direction of reducing detailed rules on APs and, by the same token, emphasizing fundamental or general principles, research on the development and the state of the art of administrative principles in the general administrative procedure acts (APAs) of selected Eastern Europe countries with a common heritage of Austrian law dating back to 1925 (Slovenia, Croatia, Macedonia and the Czech Republic) was carried out. The normative-comparative analysis reveals differences in approaches to and the pace of APAs reform and content; some countries are taking a more radical approach, mainly by following good governance dimensions. Convergence based on Council of Europe and EU initiatives is also evident. Classical guarantees against the misuse of power (principles of legality, equality, proportionality, rights of defense, etc.) are therefore crucial. The most progress seems to have been made by Croatia and the Czech Republic; by focusing on partnerships in administrative-legal relations in the sense of good administration, these two countries have, among other things, set a trend for other countries to follow.
Keywords: 330; Administrative Procedures; Eastern Europe; Good Governance; Human Rights; Principles; Rule of Law